Effect of Shooting Variations on Shooting Results in Athletes Aged 14-17 Years at Garuda II Soccer School - Langkat Regency - Agung Pratama; Muhammad Nustan Hasibuan (Journal of Indonesian Active in Sports, 2024)
This study aims to determine the effect of variations in shooting training on shooting results in athletes aged 14-17 years at Garuda II soccer school Langkat Regency in 2022. The problem that occurs in this study is the problem in the shooting process. The shooting process carried out by athletes is still monotonous and less varied. The exercises given by the coach are still few. the above occurs because it is caused by factors, namely the lack of variety of shooting exercises. The research method used is the experimental method. The sampling technique used is Purposive Sampling. The population in this study were 14 people and the number of athlete samples used was 10 people. This research was conducted for 6 weeks with a training frequency of 3 (three) times a week. Statistical calculations using the t-test. Hypothesis analysis using pre-test data and post-test data on the results of soccer shooting where the t-count analysis results obtained were 5. 231 then the value was compared with the ttable value with dk = n-1 (10-1 = 9) at a significant level Î± = 0.05 is 1.8331 thus t-count> ttable (5. 231> 1.8331). This means that Ho is rejected and Ha is accepted, it can be concluded that there is a significant influence of Shooting Exercise Variations on Shooting Results in Athletes aged 14-17 years at SSB Garuda II Langkat Regency Year 2022.